Analysis of Distinctive Features in Peruvian Sign Language (LSP) - Raico Morales, Giovana (2024)
This research focuses on the following objectives: 1) to document and describe the distinctive function that has phonological value, and 2) to identify the distinctive features in Peruvian Sign Language (PSL) in the area of manual configuration (point of articulation, movement, space) and non-manual features. In this sense, it contributes to the study of one aspect of the phonology of PSL. For this purpose, filming was carried out and language users were consulted. The methodology included fieldwork with a group of deaf people in Lima. This exploration is pioneering for LSP, since it constitutes a first effort to provide empirical evidence on the distinctive functions of manual forms in this system. To this end, it is shown that sign language has a phonology whose basic elements (distinctive features) can be identified using the same methods as in spoken languages.